Effects of Cold Compress on the Heguous Point of Meridian Large Intestine on Pain before Giving Immunization in Infants - Indra Tri Astuti; Kurnia Wijayanti; Laila Nuraini; Nopi Nur Khasanah; Herry Susanto (Universitas Airlangga, 2019)
Introduction: In basic immunizations received by infants 90% are given by injection. The immunization given by injection is a source of pain which can cause anxiety and trauma not only in infants but also for their families. Thus, it is necessary to deal with the pain with appropriate management. One non-pharmacological therapy that can be used to reduce pain is by providing cold compresses. The aim of this study was to determine the effects of cold compress on the heguous point of meridian large intestine on pain before giving immunization.Methods: This study used the quasi experimental method of posttest design with control group. This study used the instruments of Face, Legs, Activity, Cry and Consolability (FLACC) Behavioral Pain Assessment Scale to measure the pain. The sample was 42 people taken by consecutive sampling. The research data were analyzed by using the Mann Whitney test. The results obtained a p value equal to 0.023 (<0.05).Results: This indicates that there were significant differences in pain scores between the two groups, meaning that there is a significant effect of giving cold compresses to the pain score before giving immunization.Conclusion: This result explains that cold compresses carried out at the heguous point can be used as an alternative for management for non-pharmacological pain in infants during immunization.